Referendum on the Constitution dated November 6, 1994 in Albania (The associated political debate and reasons for its failure) - Nexhipi, Adelina (Technium Social Sciences Journal, 2021)
The constitutional reform is one of the most debatable reforms in the Albanian transition period. One of the most critical moments is the Referendum on the Constitution dated November 6th, 1994. The way how this process took place, helps us to understand more about the nature and the dynamics of the Albanian events during the transitional period. The purpose of this descriptive - analytic study is to describe, analyze and evaluate the Referendum on the Constitution dated November 6th, 1994, in legal, procedural and political aspect as well as its effects on political life in Albania. To meet this objective, we will be delivering an analysis of all events and decisions that took place before, during and after the Referendum on the Constitution, concentrating on the procedures that followed, debates associated to the process, political and institutional attitudes, electoral campaigns, attitudes of political parties towards the content of the draft constitution, reasons of the popular “NO” to the referendum and its consequences. The study relies on official documents of Albanian and foreign institutions (such as OSCE, Venice Commission), the press (newspapers like “Zëri i Popullit”, “Rilindja Demokratike”, “Koha Jonë”) publications from domestic and foreign scholars and memories of the protagonists. At the end, it was concluded that the lack of political consensus and the willingness of political forces to come to an agreement with each other, made the attempt to give the country a constitution failed. The result of the referendum affected the political life in the country by increasing conflicts and political intolerance among the parties. There were problems within the Democratic Party and the governing coalition too.